Origin and Classification of the Ancient South Arabian Languages - Avanzini, Alessandra (Journal of Semitic studies, 2009)
ASA (= Ancient South Arabian) documentation is testimony to a lengthy linguistic history in southern Arabia which predates the earliest written attestations. The hypothesis attributing the origin of ASA culture to immigration from the north is hard to endorse. The QAT (= Qatabanic) verb system and ASA more in general have strong parallels with the verb system of the north west of the second millennium. Just as the hypothesis of a recent wave of immigration to south Arabia is open to debate, so must the general idea of an ASA belonging to central Semitic as opposed to archaic southern Semitic be reexamined.